Analisis Kebijakan Kemitraan Kelola Sampah Antara Pemerintah Daerah Dengan Pihak Swasta di Kota Kupang - Charles Kapioru (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2022)
The implementation of waste handling policies in Kupang City with the collect-transport-waste pattern still encounters many problems. Waste management is still being carried out by the Government through the relevant agencies alone, without involving the private sector and the community on a massive scale. This study aims to find out alternative forms of policies for handling and processing household waste and household-like waste by involving the private sector and the community, as well as how the mechanism forms of public and private partnerships in its management. This study uses the Quick Survey Method, the Comparison Method with Real Experience and the Policy Alternative Selection Method. The results of the study show that the policy of public and private partnerships in waste management can be achieved by using the Public Private Partnership strategy through the implementation of the BOT system so that it can assist the government in reducing the use of APBD, also helping at the end of the contract, in which the government will obtain infrastructure from the private party. In addition, it can also open new jobs, and accelerate the process of technology transfer from the private sector to the government. It is necessary to carry out a feasibility study related to various aspects related to this partnership plan. This partnership plan is supported by waste management actors, such as: the Regional Development Planning Agency for the City of Kupang; The City of Kupang Environment and Hygiene Service, as well as District and Sub-District Heads within the Kupang City area. The Government breakthroughs are needed in the form of Regional Regulations on Waste Management in order to improve existing PERDAs.